Effect of rare earth La on hydrogen diffusion and hydrogen embrittlement susceptibility of 42CrMo martensitic steel - Hanqiang Liu; Xing Li; Chaoyun Yang; Yikun Luan; Dianzhong Li (Journal of Materials Research and Technology)
The effect of rare earth (RE) La on hydrogen diffusion and hydrogen embrittlement (HE) susceptibility of 42CrMo martensitic steel was studied by electrochemical hydrogen permeation test, hydrogen microprint technique (HMT) and slow strain rate tensile (SSRT). The results show that La modifies original Al2O3 and MnS inclusions and generates numerous well-dispersed RE inclusions. Individual RE inclusions with lower stress distribution exhibit a reduced propensity to promote HE and higher hydrogen trapping capacity than Al2O3 and MnS. Additionally, the addition of RE refines the grain structure and increases the number of high angle grain boundaries (HAGBs), effectively suppressing the propagation of hydrogen induced cracks. Compared to non-RE steel, the hydrogen diffusion coefficient of RE steel is reduced by up to 19.1%. As La content increases from 0 wt% to 0.011 wt% and 0.015 wt%, HE susceptibility of test steel decreases initially and then increases. Consequently, the appropriate addition of La can effectively impede hydrogen diffusion, improve hydrogen trapping efficiency and reduce HE susceptibility in martensitic steel.